Guidelines for Aortic Aneurysm and Aortic Dissection in Japan: Thoracic Aortic Dissection - Okada, Kenji (Japanese Journal of Vascular Surgery, 2021)
The current article summarized the section of thoracic aortic dissection in Japanese guidelines on the diagnosis and treatment of aortic aneurysm and aortic dissection revised in 2020, which could be helpful to make decisions in daily clinical practice. The revised version covered the wide spectrum of aortic dissection including the classical classification of aortic dissection, clear definition of intramural hematoma (IMH), ulcer-like projection (ULP) , penetrating atherosclerotic ulcer (PAU) to meet the needs of the times. With regard to current topics for acute type A aortic dissection, the guidelines focused on the extent of the replacement such as hemi arch replacement or total arch replacement, the utility of frozen elephant trunk, selection of surgical modes for aortic root replacement, and optimal treatments for organ malperfusion. Since the evidence for the treatment of acute type B dissection using thoracic endovascular aortic repair (TEVAR) have been accumulated, the recommendation of treatments for both complicated and uncomplicated type B dissection corresponding to the phase of time course (acute, subacute, and chronic phase) have been more clearly described compared with the previous guidelines.